A radar absorbing coating and its preparation method and application

By using the laser directly sedimentation technology to sedimentation function gradient layer, loss layer and matching layer on the surface of the aircraft, the problem of the existing radar suction material fails at high temperature, and realizes the good stealth performance of the aircraft at high temperature conditions.

CN117070933BActive Publication Date: 2025-01-28CHONGQING UNIV +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311041568.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-17
Publication Date
2025-01-28
Estimated Expiration
2043-08-17

AI Technical Summary

Technical Problem

The existing radar wave absorbing materials fail at high temperatures and cannot meet the stealth needs of modern fighter jets under high temperature conditions.

Method used

Use laser direct sedimentation technology on the surface layer of the aircraft to sediment the function gradient layer, loss layer and matching layer, and use TI, MO, and SI3N4 mixed powder, SIC powder and SI3N4 powder as raw materials, forming a good absorption, high temperature resistance, resistance to resistance to resistance Rador, hardness, and bending strength radar suction coating.

Benefits of technology

The good stealth performance of the aircraft under high temperature conditions improves the overall performance and application of the radar suction coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117070933B_ABST
    Figure CN117070933B_ABST
Patent Text Reader

Abstract

The present invention provides a radar absorbing coating and a preparation method and application thereof. The radar absorbing coating provided by the present invention comprises a functional gradient layer, a loss layer and a matching layer which are sequentially stacked and deposited on the surface of a substrate; the stacking deposition method is direct laser deposition, and the raw materials used for depositing the functional gradient layer, the loss layer and the matching layer are Ti, Mo and Si3N4 mixed powder, SiC powder and Si3N4 powder. The radar absorbing coating provided by the present invention has good wave absorption, high temperature resistance, wear resistance, hardness and bending strength, and applying it to the surface of an aircraft can make the aircraft have good stealth performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of radar absorbing coatings, and in particular relates to a radar absorbing coating and a preparation method and application thereof. Background Art

[0002] Radar stealth technology has very important military significance for improving the battlefield survival and penetration capability of weapons. Radar stealth technology refers to the use of advanced technical means to accurately control and reduce the radar reflection signal of weapons and equipment, making it difficult to be discovered, identified and attacked in the detection environment, thereby achieving effective protection of the target. The main ways to achieve radar stealth technology are shape technology and radar absorbing material technology. Shape technology is to reduce the radar cross section (RCS) by designing the appearance of the target, and radar absorbing material technology is to apply radar absorbing materials (RAM) on the target to convert electromagnetic waves into heat energy and attenuate radar waves to achieve radar stealth. Compared with shape stealth technology, radar absorbing coatings (RACs) have good absorbing effect, simple process and low design difficulty, so they have become a research hotspot in stealth technology.

[0003] As modern fighter planes are getting faster and faster, the surface temperature caused by the friction between the aircraft and the air reaches 700℃ or even higher. The pitot tube under high temperature conditions has a strong reflection of radar waves, which seriously affects the stealth performance of the fighter plane. Magnetic absorbent-filled polymer-based composite materials will lose their magnetism and the polymer matrix will decompose at high temperatures, so they cannot be used for radar absorbing stealth of the above-mentioned high-temperature components. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a radar absorbing coating and a preparation method and application thereof. The radar absorbing coating provided by the present invention has good absorption, high temperature resistance, wear resistance, hardness and bending strength. Applying it to the surface of an aircraft can enable the aircraft to have good stealth performance.

[0005] The present invention provides a radar absorbing coating, comprising: a functional gradient layer, a loss layer and a matching layer sequentially stacked and deposited on a substrate surface;

[0006] The stacked deposition method is laser direct deposition, and the raw materials used for depositing the functional gradient layer, the loss layer and the matching layer are Ti, Mo and Si3N4 mixed powder, SiC powder and Si3N4 powder in sequence.

[0007] Preferably, the content of Ti in the mixed powder is 5-15wt%; the content of Mo in the mixed powder is 5-15wt%; and the content of Si3N4 in the mixed powder is 70-90wt%.

[0008] Preferably, the content of Ti in the mixed powder is 10wt%; the content of Mo in the mixed powder is 10wt%; and the content of Si3N4 in the mixed powder is 80wt%.

[0009] Preferably, the thickness of the functional gradient layer is 0.1 to 1.5 mm.

[0010] Preferably, the lossy layer has a thickness of 0.1 to 1.5 mm.

[0011] Preferably, the matching layer has a thickness of 0.1 to 1.5 mm.

[0012] The present invention provides a method for preparing the radar absorbing coating described in the above technical solution, comprising the following steps:

[0013] Using Ti, Mo and Si3N4 mixed powder, SiC powder and Si3N4 powder as raw materials in sequence, laser direct deposition technology is used to deposit functional gradient layers, loss layers and matching layers on the surface of the substrate to obtain a radar absorbing coating.

[0014] Preferably, the bulk density of the mixed powder is 2.5 to 3.5 g / cm 3 , particle size is 50-150 μm; the bulk density of the SiC powder is 2.5-3.5 g / cm 3 , particle size is 50-150 μm; the bulk density of the Si3N4 powder is 2.5-3.5 g / cm 3 , particle size is 50~150μm.

[0015] Preferably, the laser power during the deposition is 200-400 W, the laser scanning speed is 30-50 mm / s, the spot diameter is 2-3 mm, the protective gas flow rate is 3-8 L / min, and the cooling time between two adjacent deposition operations is 20-40 s.

[0016] The present invention provides an aircraft, the outer surface of which is provided with the radar absorbing coating described in the above technical solution or the radar absorbing coating prepared by the preparation method described in the above technical solution.

[0017] Compared with the prior art, the present invention provides a radar absorbing coating and its preparation method and application. The radar absorbing coating provided by the present invention includes a functional gradient layer, a loss layer and a matching layer which are sequentially stacked and deposited on the surface of a substrate; the stacking deposition method is laser direct deposition, and the raw materials used for depositing the functional gradient layer, the loss layer and the matching layer are Ti, Mo and Si3N4 mixed powder, SiC powder and Si3N4 powder. In the present invention, the outermost matching layer is used to adjust the complex magnetic permeability and complex dielectric constant of the material to make the electromagnetic wave pass through without reflection as much as possible; the middle loss layer is used to convert the electromagnetic wave passing through the matching layer into heat energy and effectively absorb it; the functional gradient layer close to the substrate surface can effectively improve the thermal expansion coefficient mismatch and the thermal stress problem caused by the temperature gradient, and when the radar absorbing coating is prepared by laser direct deposition technology, the functional gradient layer can also improve the situation where the substrate metal elements are precipitated into the radar absorbing coating during the deposition process; the substrate surface is equivalent to a reflective layer, which can reflect a small amount of electromagnetic waves passing through the loss layer back to the loss layer for absorption again. The radar absorbing coating provided by the present invention has good absorbing properties, high temperature resistance, wear resistance, hardness and bending strength. Applying the radar absorbing coating to the surface of an aircraft can enable the aircraft to have good stealth performance.

[0018] Moreover, the radar absorbing coating provided by the present invention is prepared by laser direct deposition technology. As a rapid prototyping technology, laser direct deposition technology has a fast cooling speed; multiple materials can be deposited in situ at one time through multiple powder feeding devices; the metal-ceramic transition zone can be controlled; the heat source input and distortion are small; the dilution rate of the coating is low; it is metallurgically bonded to the substrate; the thickness of the coating is controllable; selective deposition can be performed with low material consumption, and it has the ability to use powder materials to prepare a dense 3D structure at one time, and realize the one-time preparation of a multi-layer ceramic composite structure on a metal substrate, and there is no need to post-process the formed parts; therefore, laser direct deposition technology is very suitable for preparing the radar absorbing coating of the multi-layer composite structure provided by the present invention, and can effectively control the deposition of each layer structure to improve the quality of the finished product. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0020] Figure 1 A schematic diagram of the structure of a radar absorbing coating provided in an embodiment of the present invention;

[0021] Figure 2Macroscopic morphology of the functional gradient layer, loss layer and matching layer provided in Example 1 of the present invention;

[0022] Figure 3 The XRD pattern of the surface of the radar absorbing coating of Example 1 provided by the present invention;

[0023] Figure 4 A load-displacement curve diagram of the radar absorbing coating sample of Example 1 provided by the present invention;

[0024] Figure 5 A fracture morphology diagram of a radar absorbing coating sample of Example 1 provided by the present invention;

[0025] Figure 6 The radar absorbing coating sample of Example 1 provided by the present invention corresponds to Figure 5 Microscopic image of the fracture morphology of the A1 region;

[0026] Figure 7 The radar absorbing coating sample of Example 1 provided by the present invention corresponds to Figure 5 Microscopic image of the fracture morphology of the A2 region;

[0027] Figure 8 This is a fracture morphology diagram of the radar absorbing coating sample of Example 1 provided by the present invention;

[0028] Fig. 9 A fracture morphology diagram of the coating of the radar absorbing coating sample of Example 1 provided by the present invention;

[0029] Fig.10 A sliding time-friction coefficient curve diagram of the RACs and substrate and Si3N4 ball provided in an embodiment of the present invention;

[0030] Fig.11 A diagram showing the wear of RACs and substrates provided in an embodiment of the present invention;

[0031] Fig.12 A bar graph of the wear rates of RACs and substrates provided by embodiments of the present invention;

[0032] Fig.13 SEM images of the worn surfaces of RACs and substrates provided in embodiments of the present invention;

[0033] Fig.14 A Vickers hardness bar graph provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The present invention provides a radar absorbing coating, see Figure 1 , including: a functional gradient layer (FGC), a loss layer and a matching layer deposited sequentially on the surface of a substrate.

[0036] In the radar absorbing coating provided by the present invention, the stacked deposition method is laser direct deposition, and the raw materials used for depositing the functional gradient layer, the loss layer and the matching layer are Ti, Mo and Si3N4 mixed powder, SiC powder and Si3N4 powder respectively.

[0037] In the radar absorbing coating provided by the present invention, the functional gradient layer (FGC) can effectively improve the thermal expansion coefficient mismatch and thermal stress problems caused by temperature gradient, and when the radar absorbing coating is prepared by laser direct deposition technology, the functional gradient layer can also improve the situation where the base metal elements are precipitated into the radar absorbing coating during the deposition process.

[0038] In the radar absorbing coating provided by the present invention, the components of the mixed powder used for depositing the functional gradient layer include Ti, Mo and Si3N4; the content of Ti in the mixed powder is preferably 5-15wt%, specifically 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 10.5wt%, 11wt%, 11.5wt%, 12wt%, 12.5wt%, 13wt%, 13.5wt%, 14wt%, 14.5wt% or 15wt%, most preferably 10wt%; the content of Mo in the mixed powder is preferably 5-15wt%, specifically 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5 %, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 10.5wt%, 11wt%, 11.5wt%, 12wt%, 12.5wt%, 13wt%, 13.5wt%, 14wt%, 14.5wt% or 15wt%, and 10wt% is most preferred; the content of Si3N4 in the mixed powder is preferably 70-90wt%, specifically 70wt%, 71wt%, 72wt%, 73wt%, 74wt%, 75wt%, 76wt%, 77wt%, 78wt%, 79wt%, 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt% or 90wt%, and 80wt% is most preferred.

[0039] In the radar absorbing coating provided by the present invention, the thickness of the functionally gradient layer is preferably 0.1-1.5 mm, specifically 0.1 mm, 0.13 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.42 mm, 0.45 mm, 0.5 mm, 0.55 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm or 1.5 mm.

[0040] In the radar absorbing coating provided by the present invention, the loss layer is used to convert the electromagnetic waves passing through the matching layer into heat energy and effectively absorb them; the thickness of the loss layer is preferably 0.1-1.5 mm, specifically 0.1 mm, 0.13 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.42 mm, 0.45 mm, 0.5 mm, 0.55 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm or 1.5 mm.

[0041] In the radar absorbing coating provided by the present invention, the matching layer is used to adjust the complex magnetic permeability and complex dielectric constant of the material to allow electromagnetic waves to pass through without reflection as much as possible; the thickness of the matching layer is preferably 0.1-1.5 mm, specifically 0.1 mm, 0.13 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.42 mm, 0.45 mm, 0.5 mm, 0.55 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm or 1.5 mm.

[0042] In the radar absorbing coating provided by the present invention, the substrate is equivalent to a reflective layer, which can reflect a small amount of electromagnetic waves that pass through the loss layer back to the loss layer for absorption again; the material of the substrate includes but is not limited to nickel-based high-temperature alloys, titanium alloys or stainless steel, specifically IN718 high-temperature alloy.

[0043] The present invention also provides a method for preparing the radar absorbing coating described in the above technical solution, comprising the following steps:

[0044] Using Ti, Mo and Si3N4 mixed powder, SiC powder and Si3N4 powder as raw materials in sequence, laser direct deposition technology is used to deposit functional gradient layers, loss layers and matching layers on the surface of the substrate to obtain a radar absorbing coating.

[0045] In the preparation method provided by the present invention, the contents of Ti, Mo and Si3N4 in the mixed powder have been introduced in the previous text and will not be repeated here; the bulk density of the mixed powder is preferably 2.5 to 3.5 g / cm 3 , specifically 2.5g / cm 3 , 2.6g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 , 3g / cm 3 、3.1g / cm3 、3.2g / cm 3 、3.3g / cm 3 、3.4g / cm 3 or 3.5g / cm 3 ; The particle size of the mixed powder is preferably 50 to 150 μm, specifically 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm.

[0046] In the preparation method provided by the present invention, the bulk density of the SiC powder is preferably 2.5 to 3.5 g / cm 3 , specifically 2.5g / cm 3 , 2.6g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 , 3g / cm 3 、3.1g / cm 3 、3.2g / cm 3 、3.3g / cm 3 、3.4g / cm 3 or 3.5g / cm 3 ; The particle size of the SiC powder is preferably 50 to 150 μm, specifically 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm.

[0047] In the preparation method provided by the present invention, the bulk density of the Si3N4 powder is preferably 2.5 to 3.5 g / cm 3 , specifically 2.5g / cm 3 , 2.6g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 , 3g / cm 3 、3.1g / cm 3 、3.2g / cm 3 、3.3g / cm 3 、3.4g / cm 3 or 3.5g / cm 3 ; The particle size of the Si3N4 powder is preferably 50-150μm, specifically 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm or 150μm.

[0048] In the preparation method provided by the present invention, in order to make the powder obtain good fluidity, the mixed powder of Ti, Mo and Si3N4, SiC powder and Si3N4 powder are preferably dried before deposition; the drying temperature is preferably 100-150°C, specifically 100°C, 110°C, 120°C, 130°C, 140°C or 150°C; the drying time is preferably 60-180min, specifically 60min, 70min, 80min, 90min, 100min, 110min, 120min, 130min, 140min, 150min, 160min, 170min or 180min.

[0049] In the preparation method provided by the present invention, the mixed powder of Ti, Mo and Si3N4, SiC powder and Si3N4 powder are first added to the powder feeder of the laser direct deposition equipment, and then fed through the powder feeder for laser direct deposition; wherein, in order to prevent the powder from being oxidized, when the powder is added to the powder feeder, high-purity inert gas is preferably filled into the powder feeder to exclude oxygen in the powder feeder, and the high-purity inert gas is preferably argon.

[0050] In the preparation method provided by the present invention, before deposition, the surface of the substrate is preferably pretreated, and the pretreatment process preferably includes grinding, wiping and drying the substrate surface in sequence; wherein the abrasive belt used for grinding is preferably a diamond abrasive belt; the grinding rotation speed is preferably 13-15 m / s, specifically 14.6 m / s; the grinding down pressure is preferably 12-13 N, specifically 12.4 N; the grinding feed speed is preferably 10-12 mm / s, specifically 10.7 mm / s; the surface roughness of the substrate after grinding is preferably ≤0.8 μm, more preferably ≤0.7 μm, specifically 0.6717 μm; the wiping agent is preferably anhydrous ethanol.

[0051] In the preparation method provided by the present invention, the laser power during the deposition is preferably 200-400 W, specifically 200 W, 210 W, 220 W, 230 W, 240 W, 250 W, 260 W, 270 W, 280 W, 290 W, 300 W, 310 W, 320 W, 330 W, 340 W, 350 W, 360 W, 370 W, 380 W, 390 W or 400 W, most preferably 300 W; the laser scanning speed during the deposition is preferably 30-50 mm / s, specifically 30 mm / s, 31 mm / s, 32 mm / s, 33 mm / s, 34 mm / s, 35 mm / s, 36 mm / s, 37 mm / s, 38 mm / s, 39 mm / s or 400 W. 35mm / s, 36mm / s, 37mm / s, 38mm / s, 39mm / s, 40mm / s, 41mm / s, 42mm / s, 43mm / s, 44mm / s, 45mm / s, 46mm / s, 47mm / s, 48mm / s, 49mm / s or 50mm / s, and 40mm / s is most preferred; the spot diameter during the deposition is preferably 2-3mm, specifically 2mm, 2.1mm, 2.2mm, 2.3mm, 2.4mm, 2.5mm, 2.6mm, 2.7mm, 2.8mm, 2.9mm or 3mm, and 2.5mm is most preferred.

[0052] In the preparation method provided by the present invention, the flow rate of the protective gas during the deposition is preferably 3 to 8 L / min, specifically 3 L / min, 3.5 L / min, 4 L / min, 4.5 L / min, 5 L / min, 5.5 L / min, 6 L / min, 6.5 L / min, 7 L / min, 7.5 L / min or 8 L / min, and most preferably 5 L / min.

[0053] In the preparation method provided by the present invention, the thickness of the corresponding functional layer is regulated by controlling the number of deposited layers when depositing the functional gradient layer, the loss layer and the matching layer. The cooling time between two adjacent deposition operations is preferably 20 to 40 s, specifically 20 s, 21 s, 22 s, 23 s, 24 s, 25 s, 26 s, 27 s, 28 s, 29 s, 30 s, 31 s, 32 s, 33 s, 34 s, 35 s, 36 s, 37 s, 38 s, 39 s or 40 s, and 30 s is most preferred.

[0054] The present invention also provides an aircraft, the outer surface of which is provided with the radar absorbing coating described in the above technical solution or the radar absorbing coating prepared by the preparation method described in the above technical solution.

[0055] The technical solution provided by the present invention can make the radar absorbing coating have good wave absorption, high temperature resistance, wear resistance, hardness and bending strength by optimizing the structure of the radar absorbing coating. Applying it to the surface of the aircraft can make the aircraft have good stealth performance. Moreover, the radar absorbing coating provided by the present invention is prepared by laser direct deposition technology. As a rapid prototyping technology, laser direct deposition technology has a fast cooling speed; multiple materials can be deposited in situ at one time through multiple powder feeding devices; the control of the metal-ceramic transition zone can be achieved; the heat source input and distortion are small; the dilution rate of the coating is low; it is metallurgically bonded with the substrate; the thickness of the coating is controllable; selective deposition can be performed, material consumption is small, and it has the ability to use powder materials to prepare a dense 3D structure at one time, and realize the one-time preparation of a multi-layer ceramic composite structure on a metal substrate, and there is no need to post-process the formed parts; therefore, laser direct deposition technology is very suitable for preparing the radar absorbing coating of the multi-layer composite structure provided by the present invention, and can effectively control the deposition of each layer structure and improve the quality of the finished product.

[0056] For the purpose of greater clarity, the invention is described in detail through the following embodiments.

[0057] Example 1

[0058] preparation Figure 1 The structure of radar absorbing coating is shown in the figure. The specific process is as follows:

[0059] Ti powder, Mo powder and Si3N4 powder were put into a horizontal ball mill and ground for 12 hours in a mass percentage ratio of Ti:Mo:Si3N4=10%:10%:80% to fully mix the powders to obtain a mixed powder of Ti, Mo and Si3N4 (abbreviated as FGC powder) for use; SiC powder and Si3N4 powder were also prepared for use; the performance indicators of the three powders are shown in Table 1.

[0060] Table 1 Performance index of powder

[0061]

[0062] In order to obtain good fluidity of the powder, SiC powder, Si3N4 powder and FGC powder were placed in a drying oven and kept at 120°C for 120 minutes. After the powder was cooled in the drying oven, it was immediately placed in a powder feeder and high-purity argon gas was filled in to remove oxygen in the powder feeder to prevent the powder from being oxidized.

[0063] The surface of the substrate (IN718 high-temperature alloy) was ground by belt grinding technology. The grinding process parameters are shown in Table 2. After grinding, the surface was smoother, the glossiness was stronger, and the roughness was reduced to about 0.6717 μm. Then, the stains on the surface were wiped with anhydrous ethanol and placed in a drying oven for drying.

[0064] Table 2 Grinding process parameters

[0065]

[0066] After the substrate surface is ground, the FGC powder, SiC powder and Si3N4 powder added to the powder feeder are used as raw materials in turn, and laser direct deposition is performed on the substrate surface using the process parameters listed in Table 3 to form a functional gradient layer (FGC), a loss layer and a matching layer in turn. Figure 1 Radar absorbing coating with the structure shown.

[0067] Table 3 Process parameters of laser direct deposition radar absorbing coating

[0068]

[0069]

[0070] In this embodiment, the macroscopic morphology of the three layers of the radar absorbing coating is as follows: Figure 2 As shown, Figure 2 This is a macroscopic morphology diagram of the functional gradient layer, loss layer and matching layer provided in Example 1 of the present invention.

[0071] In this embodiment, the thickness of the functional gradient layer of the obtained radar absorbing coating is 550.4 μm, the thickness of the loss layer is 420 μm, and the thickness of the matching layer is 132.2 μm.

[0072] Example 2

[0073] The radar absorbing coating prepared in Example 1 was analyzed and characterized as follows:

[0074] (1) Phase analysis

[0075] Figure 3 This is the XRD diagram of the surface of the radar absorbing coating of Example 1 provided by the present invention. Figure 3 It can be seen that the phases on the surface of the radar absorbing coating are mainly SiC, SiCN and Si. The diffraction peak of Si in the sample is relatively low, and the diffraction peaks of SiC and SiCN are relatively high. It can be seen that at high temperature, the Si3N4 directly deposited by the laser in the sample reacts with the silicon nitride generated by the direct nitridation of Si and completely transforms into SiCN under the action of amorphous carbon.

[0076] (2) Dielectric constant

[0077] High-temperature radar absorbing coatings (RACs) are usually dielectric loss RACs. Polarization loss is one of the types of absorption and attenuation mechanisms of dielectric loss RACs. The complex dielectric constant ε is an important parameter that reflects the polarization ability of dielectric loss RACs in an electromagnetic field. The complex dielectric constant is generally expressed in complex form as shown in formula (1). Its real part reflects the change in state during electromagnetic wave propagation, such as changes in phase, phase velocity, wave impedance, etc.; its imaginary part represents the measure of the loss caused by the rearrangement of the material's electric dipole moment under the action of an external electric field, characterizing the material's electrical loss characteristics and reflecting the electromagnetic wave attenuation and energy loss characteristics of the material.

[0078] ε=ε′-jε″ Formula (1).

[0079] In this embodiment, the dielectric constant ε of the RACs prepared in Example 1 was measured by a network analyzer according to GB / T1409-2006 at a frequency of 15 GHz to be 7.382, the real part ε′ of the dielectric constant was 7.254, the imaginary part ε″ was 4.32125, and the loss factor tanδ=0.5833; the larger the imaginary part of the dielectric constant, the larger the tanδ loss factor, the greater the energy loss of the electromagnetic wave, and the more conducive to the absorption of the electromagnetic wave. It can be seen that the RACs prepared by laser direct deposition in Example 1 have stealth performance.

[0080] (3) Analysis of flexural strength and fracture morphology

[0081] One of the simplest methods for evaluating the mechanical strength of a coating-substrate bond is the three-point bending test. Figure 4The load-displacement curve of the radar absorbing coating sample of Example 1 provided by the present invention is shown. By observing the load-displacement curve, the load shows a linear growth trend before point A. At this stage, the coating and the base material deform elastically and harmoniously, and continuous small cracks are generated inside the material to form internal defects, but surface cracks are not generated. After reaching point A (elastic limit point), crack initiation begins at the preset crack. After point A, the slope of the curve begins to decrease, and the material undergoes a transition from elastic deformation to plastic deformation. During the period from point A to point B, the molecular cohesion inside the material resists the external load force, and the crack does not expand. After reaching point B, a crisp sound occurs, and the coating reaches the fracture threshold. The coating loses the ability to resist crack expansion. At this time, the load is the critical load of coating fracture, 3072N. Since the coating and the substrate are metallurgically bonded, the coating will not peel off from the interface after fracture; the force continues to be applied, and the crack continues to expand downward, accompanied by the generation of multiple cracks at the crack tip. The substrate breaks multiple times, resulting in multiple mutations in the load-displacement curve. During the test, whenever the load curve shows a sudden decline, the sound of fracture can be clearly heard; it is completely broken when the bending displacement is 4.2mm and the bending load is 3078N; the flexural strength is 1282.5MPa, which is about 23.5% higher than the flexural strength of 1038MPa of Si3N4 / SiC gradient material prepared by sintering process.

[0082] Figures 5 to 9 The results of SEM analysis of the fracture surface of RACs samples after three-point bending are shown in Figure 2. Figure 5 This is a fracture morphology diagram of the radar absorbing coating sample of Example 1 provided by the present invention. Figure 6 The radar absorbing coating sample of Example 1 provided by the present invention corresponds to Figure 5 The fracture morphology of the A1 region is shown in the micrograph. Figure 7 The radar absorbing coating sample of Example 1 provided by the present invention corresponds to Figure 5 The fracture morphology micrograph of the A2 region. Figure 8 This is a fracture morphology diagram of the radar absorbing coating sample of Example 1 provided by the present invention. Fig. 9 This is a fracture morphology diagram of the coating of the radar absorbing coating sample of Example 1 provided by the present invention.

[0083] pass Figure 5 Obvious necking phenomenon can be observed, and a shallow notch is formed at the edge of the fracture morphology; area A1 is the microscopic image of the fracture morphology of the substrate ( Figure 6 ), pores and cracks can be clearly observed; A2 area is the fracture morphology of the coating ( Figure 7 ), it was observed that there was a very obvious crack, which was on the surface of the unmelted particles, indicating that the unmelted particles would cause stress concentration in the structure and promote the initiation and expansion of cracks.

[0084] pass Figure 8 It can be observed that there are many small dimples gathered around the large dimples, and tear ridges are also observed, indicating that when stretched by external force, it will not break immediately but tear, stretch and deform inside the material first; Fig. 9 The cleavage plane can be clearly observed. During the fracture process, the dendritic precipitates will cause stress to increase. When the critical stress of crack propagation of the material is lower than the yield strength, the crack will propagate along the dissociation plane, and the twins produced successively will collide and produce dislocation slip. The dimples and tear ridges are classic features of the ductile fracture mode, and the cleavage plane is a typical feature of the brittle fracture mode. Therefore, the main fracture mode of the substrate is ductile fracture, and the main fracture mode of the coating is brittle fracture.

[0085] (4) Friction and wear

[0086] (4.1) Friction coefficient

[0087] In order to evaluate the friction and wear performance of RACs, dry friction tests were carried out on the RACs prepared in Example 1 and the substrate material without deposition at 40N. The results are as follows: Fig.10 As shown, Fig.10 The sliding time-friction coefficient curve of the RACs and substrate provided in the embodiment of the present invention and the Si3N4 ball.

[0088] The friction process of the sample generally includes a running-in stage and a stabilization stage. Fig.10 The sliding time-friction coefficient curve in is consistent with this point. It can be seen that the friction coefficients of RACs and substrates first increase and then tend to stabilize; the friction coefficient increases sharply in the initial running-in stage, which is caused by the high roughness of the friction contact surface. As the wear distance increases, it enters a stable stage, and the friction coefficient fluctuates within a stable range and shows a state of dynamic equilibrium; after fitting the friction coefficients of RACs and substrates, it is found that the friction coefficient of the coating is stable at around 0.0708, and the friction coefficient of the substrate is stable at around 0.1432. The friction coefficient of RACs is about 50% smaller than that of the substrate, indicating that RACs has good wear resistance.

[0089] (4.2) Wear amount

[0090] The wear resistance of the coating is one of the important indicators for evaluating the performance of laser direct deposition coatings. Wear resistance can be evaluated by the size of the wear rate. There are two methods for measuring the wear rate: using the wear volume to represent the wear rate, and using instruments and formulas to calculate the wear volume of the sample; the other is to use the weight loss to represent the wear rate of the sample, and use an electronic balance to measure the mass of the sample before and after friction and wear to obtain the weight loss of the sample. Since the friction movement distance is small and the friction time is short during the wear process, the weight loss of the coating is relatively small, and the accuracy of the electronic balance is easily affected by factors such as voltage, temperature, air flow vibration, and operator, it is inaccurate to use an electronic balance to obtain the weight loss to evaluate the wear resistance of the sample; therefore, this patent uses a method of calculating the wear volume to evaluate the wear resistance. When the SiC ceramic ball of the grinding pair contacts the sample, the surface of the sample intersects with the ball as a plane, and the intersection figure is a circle. The width of the wear mark is the diameter of the circle. The volume below the cross section of the SiC ceramic ball is calculated as the wear volume, and the wear volume loss per unit time is quantitatively calculated as a representation of the volume wear rate. The wear volume (W V ) and wear rate (W R ) is calculated according to formulas (2) and (3).

[0091]

[0092]

[0093] In formulas (2) to (3), R is the radius of the SiC ceramic ball in the grinding pair, R = 4.7625 mm, b is the wear width, l is the sliding distance, and N is the loading load.

[0094] The microscopic morphology of the wear scars of the RACs prepared in Example 1 and the substrate material without deposition after wear is as follows: Fig.11 As shown, Fig.11 The wear condition diagram of RACs and substrates provided in the embodiment of the present invention, wherein (a) is RACs and (b) is substrates. Fig.11 It can be seen that compared with the scratches on the coating, the wear marks of the substrate without coating deposition are larger and the wear is more serious; the wear width h is measured by taking the part with more uniform wear width of RACs and substrate, and ensuring that the sliding distance of the taken part is the same; then it is substituted into the formula to estimate the amount of wear.

[0095] The wear rates of the RACs prepared in Example 1 and the substrate material without deposition are as follows: Fig.12 As shown, Fig.12 A bar graph showing the wear rates of RACs and substrates provided by embodiments of the present invention. Fig.12 It can be seen that the wear rate of RACs prepared in Example 1 is 7.9×10 -4 mm 3 N-1 mm -1 The wear rate of the substrate material without deposition is 11.3×10 -4 mm 3 N -1 mm -1 ; Obviously, the wear rate of RACs is about 30.08% lower than that of the substrate; this is because there are hard phases such as SiC and SiCN in the coating. These hard phases increase the hardness of the coating while reducing the adhesion between the SiC friction pair and the surface of the deposited layer during the friction process. When severe wear occurs, the particles of the hard phases are first broken, which has an anti-wear effect on the wear of RACs. Therefore, RACs have good wear resistance.

[0096] (4.3) Wear mechanism

[0097] See also Fig.13 , Fig.13 SEM images of the wear surfaces of RACs and substrates provided in embodiments of the present invention, wherein (a) is an SEM image of the wear surface of the substrate material without deposition, (b) is a partial enlarged image of (a), (c) is an SEM image of the wear surface of the RACs prepared in Example 1, and (d) is a partial enlarged image of (c).

[0098] Combination Fig.13 (a) and Fig.13 (b) It can be seen that the wear marks on the substrate are clear, and there is obvious grinding adhesion at the edge of the wear marks. During the dry friction process, the friction heat is generated much faster than its conduction speed. The strong local heat produces serious adhesion on the wear surface, resulting in material transfer, so that SiC particles exist in the grinding, which greatly increases the friction coefficient and leads to an increase in the wear rate. Fig.13 (b) It was found that there were large cracks in the wear marks and their direction was perpendicular to the direction of wear and sliding. In addition, it was found that a large number of abrasive particles were generated in the substrate during the sliding friction process, which were pressed into the friction surface by the normal load. These micro-peaks could fit into each other and produce collisions. The material produced groove-shaped wear marks due to plastic deformation, forming a plowing effect. During repeated friction, the wrinkles broke into fragments and fell off. It can be seen that the wear mechanism of the substrate is mainly plowing effect, adhesive wear and abrasive wear.

[0099] Combination Fig.13 (c) and Fig.13 (d) It can be found that the worn surface of RACs shows a flat morphology and there is no grinding accumulation at the edge of the wear scar, so it has a lower friction coefficient; Fig.13(d) It was found that there were pits of different sizes and depths on the wear surface. This is because when the SiC ceramic ball of the grinding pair slides on the RACs surface, the cyclic stress in the contact area exceeds the fatigue strength of the material, and cracks are initiated in the surface layer and gradually expand, and finally the material above the cracks breaks and peels off. This feature is a typical fatigue wear. In addition, it was found that there were many abrasive particles on the wear surface. The small abrasive particles generated during the wear process can form hard micro-protrusions. Under the push of the friction pair, the hard abrasive particles slide on the coating surface and cause the surface material to fall off. Because some ceramics are segregated, the bonding force decreases, showing a typical abrasive wear phenomenon. However, these hard micro-protrusions can effectively bear the load and play an important role in resisting the plastic deformation of the coating. Therefore, depositing RACs on the substrate can effectively improve its wear resistance.

[0100] (5) Vickers hardness

[0101] The Vickers hardness of the RACs coating was tested by a nanoindenter. The Vickers hardness of the bonding area between the coating and the substrate and the substrate is shown in Figure 2. Fig.14 As shown, Fig.14 A Vickers hardness bar graph provided by an embodiment of the present invention. Fig.14 It can be seen that the Vickers hardness of the RACs coating is 852.28HV, the Vickers hardness of the bonding area between the coating and the substrate is 531.76HV, the Vickers hardness of the substrate is 168.39HV, and the Vickers hardness of the RACs is about 4 times higher than that of the substrate; as the hardness value increases in the deposition direction, it means that FGC has greatly improved the precipitation of substrate metal elements into the coating.

[0102] Example 3

[0103] The radar absorbing coating was prepared by referring to the specific process of Example 1, except that the composition of the FGC powder was adjusted to: 15% Ti, 15% Mo and 70% Si3N4.

[0104] The performance of the radar absorbing coating prepared in this example was evaluated according to the evaluation method provided in Example 2. The results showed that although the radar absorbing coating also has wave absorption and high temperature resistance, its comprehensive performance is not as good as that of Example 1.

[0105] Example 4

[0106] The radar absorbing coating was prepared by referring to the specific process of Example 1, except that the composition of the FGC powder was adjusted to: 5% Ti, 5% Mo and 90% Si3N4.

[0107] The performance of the radar absorbing coating prepared in this example was evaluated according to the evaluation method provided in Example 2. The results showed that although the radar absorbing coating also has wave absorption and high temperature resistance, its comprehensive performance is not as good as that of Example 1.

[0108] Comparative Example 1

[0109] The radar absorbing coating was prepared by referring to the specific process of Example 1, except that the loss layer and the matching layer were combined into one layer, that is, the sequential deposition of SiC powder and Si3N4 powder was adjusted to directly deposit a mixed powder of SiC and Si3N4; in this comparative example, the content of SiC in the mixed powder was 15wt%, and the total deposition thickness of the mixed powder was about 550μm.

[0110] The performance of the radar absorbing coating prepared in this comparative example was evaluated according to the evaluation method provided in Example 2. The results showed that the absorbing performance of the radar absorbing coating was far inferior to that of Example 1.

[0111] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A radar absorbing coating, characterized in that: include: A functional gradient layer, a loss layer and a matching layer are sequentially stacked and deposited on the surface of the substrate; The stacked deposition method is direct laser deposition, and the raw materials used for depositing the functional gradient layer, the loss layer and the matching layer are Ti, Mo and Si3N4 mixed powder, SiC powder and Si3N4 powder in sequence; The content of Ti in the mixed powder is 5-15wt%; the content of Mo in the mixed powder is 5-15wt%; the content of Si3N4 in the mixed powder is 70-90wt%; The thickness of the functional gradient layer is 0.1-1.5 mm; the thickness of the loss layer is 0.1-1.5 mm; and the thickness of the matching layer is 0.1-1.5 mm.

2. The radar absorbing coating according to claim 1, characterized in that: The content of Ti in the mixed powder is 10wt%; the content of Mo in the mixed powder is 10wt%; and the content of Si3N4 in the mixed powder is 80wt%.

3. A method for preparing a radar absorbing coating according to any one of claims 1 to 2, characterized in that: The following steps are involved: Using Ti, Mo and Si3N4 mixed powder, SiC powder and Si3N4 powder as raw materials in sequence, laser direct deposition technology is used to deposit functional gradient layers, loss layers and matching layers on the surface of the substrate to obtain a radar absorbing coating.

4. The preparation method according to claim 3, characterized in that: The bulk density of the mixed powder is 2.5 to 3.5 g / cm 3 , particle size is 50-150 μm; the bulk density of the SiC powder is 2.5-3.5 g / cm 3 , particle size is 50-150 μm; the bulk density of the Si3N4 powder is 2.5-3.5 g / cm 3 , particle size is 50~150μm.

5. The preparation method according to claim 3, characterized in that: The laser power during the deposition is 200-400W, the laser scanning speed is 30-50mm / s, the spot diameter is 2-3mm, the protective gas flow rate is 3-8L / min, and the cooling time between two adjacent deposition operations is 20-40s.

6. An aircraft, characterized in that: The outer surface of the aircraft is provided with the radar absorbing coating according to any one of claims 1 to 2 or the radar absorbing coating prepared by the preparation method according to any one of claims 3 to 5.

Citation Information

Patent Citations

  • Method for modifying functional coat of gradient dispersed stuffing grains, and application

    CN101003701A

  • Microwave absorbing ceramic of silicon carbide compound material and preparation method thereof

    CN102211938A